Study of the structure and properties of deposited layers of NiCrBSi alloy, modified with composite material - Sytnykov, P. A. (Slovenian Research and Innovation Agency, 2023)
The structure and properties of deposited layers with a self-fluxing PG-10N-01 alloy of the NiCrBSi system, which is modified with composite material obtained by selfpropagating high-temperature synthesis, were studied. Powders of titanium, technical carbon, refractory clay, aluminum, iron oxide, and PT-NA-01 thermosetting powder are used as the initial components of the modifying composite material. The powders were mechanically activated in a ball mill, pressed into a cylindrical sample, and then subjected to the process of self-propagating high-temperature synthesis. The deposition of the samples was carried out with a non-fusible graphite electrode with a diameter of 9.5 mm, at a current of 110 A, using an inverter power source SV-290NK. It was established that the structure of the layer deposited with the PG-10N-01 alloy consists of a solid solution based on nickel (γ-Ni) and a eutectic formed on its basis with Ni₃B boride. Single inclusions of carbides of chromium Cr3C₂ and boron B₄C were also detected in the deposited layer. When adding a modifying composite material to the PG-10N-01 alloy, the structure of the deposited layer consists of γ-hard solution and eutectics, strengthened by carbides of titanium TiC and silicon SiC, which increase the microhardness and wear resistance of the layer. The microhardness of the layer deposited with the composite material, which contained 10% of the modifying component, is 660 HV, which exceeds the microhardness of the layer deposited with the PG-10N-01 alloy, which is equal to 510 HV. Based on the results of the research, operational tests of the set of duckfoot blades of the KPP-8 semi-trailer cultivator, aggregated with the New Holland T 6090 tractor, were carried out in the conditions of the Kamianuvatka farm (Novoukrainka district, Kirovohrad region). Based on the tests, it was proved that the relative wear resistance of duckfoot blades made of 65G steel, strengthened on the reverse side according to the "toe-working blade" scheme by depositing a layer of composite material is 1.7 times greater compared to the wear resistance of blades made by standard technology logic.

Досліджено структуру й властивості шарів, наплавлених самофлюсівним сплавом системи NiCrBSi марки ПГ-10Н-01, модифікованим композиційним матеріалом, отриманим самопоширюваним високотемпературним синтезом. Як вихідні компоненти модифікуючого композиційного матеріалу використано порошки титану, технічного вуглецю, вогнетривкої глини, алюмінію, оксиду заліза й термореагуючого порошку ПТ-НА-01. Порошки були механічно активовані в кульовому млині, спресовані в циліндричний зразок, після чого піддані процесу самопоширюваного високотемпературного синтезу. Наплавлення зразків здійснювали неплавким графітовим електродом діаметром 9,5 мм, при струмі 110 А із застосуванням інверторного джерела живлення СВ-290НК. Встановлено, що структура шару, наплавленого сплавом ПГ-10Н-01, складається з твердого розчину на основі нікелю (γ-Ni) й евтектики, утвореної на його основі з боридом Ni₃B. Також в наплавленому шарі виявлені поодинокі включення карбідів хрому Cr3C₂ і бору B₄C. При додаванні до сплаву ПГ-10Н-01 модифікуючого композиційного матеріалу структура наплавленого шару складається з γ-твердого розчину й евтектики, зміцнених карбідами титану TiC і кремнію SiC, які підвищують мікротвердість і зносостійкість шару. Мікротвердість шару, наплавленого композиційним матеріалом, який містив 10% модифікуючої складової, становить 660 HV, що перевищує мікротвердість шару, наплавленого сплавом ПГ-10Н-01, яка дорівнює 510 HV. За результатами досліджень проведені експлуатаційні випробування в умовах Фермерського господарства «Кам’януватка» (Новоукраїнський район, Кіровоградська область) комплекту стрілчастих лап напівпричіпного культиватору КПП-8, агрегованого з трактором New Holland T 6090. На основі проведених випробувань доведено, що відносна зносостійкість стрілчастих лап, виготовлених зі сталі 65Г, зміцнених зі зворотного боку за схемою «носок-робочі леза» шляхом наплавлення шару композиційного матеріалу, в 1,7 рази більша порівняно з зносостійкістю лап, виготовлених за стандартною технологією.
Дослідження структури й властивостей наплавлених шарів NiCrBSi-сплаву, модифікованого композиційним матеріалом
Keywords: self-propagating high-temperature synthesis; charge; composite material; deposition; deposited layer; carbide; самопоширюваний високотемпературний синтез; шихта; композиційний матеріал; наплавлення; наплавлений шар; карбід